2011
DOI: 10.1016/j.currproblcancer.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions for Cancer-Induced Cachexia

Abstract: Cancer-induced cachexia remains a significant cause of morbidity and mortality in cancer treatment. Cancer research and development continues at an aggressive pace and yet a degree of cancer-induced cachexia is experienced by up to 80% of advanced stage cancer patients. Unfortunately, there are no established treatment regimens for this condition. Weight loss and fatigue consistently appear in patient oncologic histories and progress notes. However, few oncologists fully understand the pathologic mechanisms ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 140 publications
(142 reference statements)
1
81
0
3
Order By: Relevance
“…This condition has deleterious effects on patient quality of life; make them more susceptible to the toxic effects of radiotherapy and chemotherapy and consequently limits treatment outcome and elevates mortality rate [189][190][191]. After one-third weight loss, death became imminent due to respiratory failure caused by diaphragm muscle devastating [188,192]. Cachexia-induced muscle loss is a result of decrease in synthesis/degradation ratio of protein through imbalance of ubiquitin-proteasome as well as dystrophin glycoprotein complex pathways [193][194][195].…”
Section: Cancer Cachexiamentioning
confidence: 98%
See 1 more Smart Citation
“…This condition has deleterious effects on patient quality of life; make them more susceptible to the toxic effects of radiotherapy and chemotherapy and consequently limits treatment outcome and elevates mortality rate [189][190][191]. After one-third weight loss, death became imminent due to respiratory failure caused by diaphragm muscle devastating [188,192]. Cachexia-induced muscle loss is a result of decrease in synthesis/degradation ratio of protein through imbalance of ubiquitin-proteasome as well as dystrophin glycoprotein complex pathways [193][194][195].…”
Section: Cancer Cachexiamentioning
confidence: 98%
“…It is believed that near four fifths of advanced stage cancer patients experience cancer-induced cachexia [185]. Cancer-induced cachexia is responsible of about one-fifth of cancer-related death especially in patients who suffer from head and neck, pancreatic, lung, colorectal, gastric, liver, esophageal, malignancies [186][187][188]. This condition has deleterious effects on patient quality of life; make them more susceptible to the toxic effects of radiotherapy and chemotherapy and consequently limits treatment outcome and elevates mortality rate [189][190][191].…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…The mechanism behind this effect is unclear. Reduced caloric intake is another key component of cancer cachexia and opposing this is part of the current strategy to treat cachexia in cancer patients through administration of appetite stimulants and nutritional support (34). Myostatin expression has been shown to increase in specific muscles and contribute to muscle atrophy during food deprivation in mice (35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that an inflammatory reaction to a local tumor can also trigger a cascade of systemic inflammation that eventually lead to development of anorexia and catabolic processes, such as muscle proteolysis and lipolysis, the early stage of fatigue and cachexia [112]. Several clinical trials have been reported using EPA or marine fish oil (EPA + DHA) in purified form or in the form of oral supplements in an effort to prevent or reduce weight and muscle loss in cancer patients.…”
Section: Clinical Trials Using N-3 Pufas For Cancer Prevention Andmentioning
confidence: 99%